Exploring an Exemplary English Lecturer's Participation in TPD and its Implementation in the Teaching and Learning Process: English - Sayit Abdul Karim; Herlina Ayu Ramadhani; Radita Nari Laksita; Gordan Matas; Septi Riana Dewi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Professional development for educators was crucial to ensure quality teaching and improved student learning outcomes. This study aimed to explore how an English lecturer at Universitas Teknologi Yogyakarta (UTY) participated in the Teacher Professional Program (TPD) program and implemented the knowledge gained into her teaching practice. This study used a qualitative case study approach, which involved one English lecturer who was selected based on criteria such as teaching experience and active participation in TPD activities. The questions were sent to the respondent through a digital messaging platform and analysed using descriptive qualitative analysis and Miles & Huberman's (1994) interactive model. The findings revealed that the lecturer is actively involved in both internal and external TPD programs. Furthermore, the internal programs focused on general pedagogical skills, while external programs were more targeted at English Language Teaching (ELT). The lecturer implemented various strategies from the PD sessions, such as process-based writing instruction, structured peer feedback, and the use of digital tools. However, challenges include the generality of the training materials and the lack of structured follow-up support. The study concluded that quality TPD implementation requires individual motivation and institutional support. PD programs should not only provide relevant content, but also offer ongoing support. The study highlights the need for more targeted, reflective, and practical PD to ensure meaningful impact in the classroom